2018
DOI: 10.31729/jnma.3440
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Awareness, and Attitude Regarding Dental Implants among Dental Interns

Abstract: Introduction: Implant therapy is an elective dental procedure of dental rehabilitative treatment. Objective of this study was to assess the knowledge, awareness, and attitude of dental interns of Nepal toward dental implants and to see associations of the responses with gender and geographic location of dental college. Methods: It was conducted from June 2016 to June 2017 after taking ethical clearance and approval from the research committee. The sample included the interns who were present at the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…When comparing the results for general implant knowledge with other studies, we found that the correct answers in our study to the five items ranged from 53% to 70.2%, which is similar to previous studies of Nepalese dentists, ranging from 51.7% to 78.2% for the same questions in two studies [17,20]. To the best of our knowledge, there are no similar local studies assessing general implant knowledge.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…When comparing the results for general implant knowledge with other studies, we found that the correct answers in our study to the five items ranged from 53% to 70.2%, which is similar to previous studies of Nepalese dentists, ranging from 51.7% to 78.2% for the same questions in two studies [17,20]. To the best of our knowledge, there are no similar local studies assessing general implant knowledge.…”
Section: Discussionsupporting
confidence: 87%
“…The questionnaire used in this study was derived from four validated questionnairesin previous studies [17,18,20,21] with modifications, and a pilot testing was carried out among 10 participants to evaluate the questions in terms of syntax, organization, order, logical sequence, content, grammar, and clarity of meaning.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominance of males over females was also reported in a previous study, which attributed this finding to other factors, stating that the dental profession worldwide is generally more male dominated [31]. However, this finding is inconsistent with other studies [32][33][34][35]. One of these studies, which was conducted in India, attributed this shift to the growing increase in females over males that has occurred over several years [33].…”
Section: Discussionmentioning
confidence: 74%
“…In a similar study done to assess the knowledge of dental interns of Nepal 58.6% said the main advantage of dental implants as compared to other tooth-replacement modalities is they are more conservative and 51.07% said case selection to be the most important factor for implant success. 24 This suggests that undergraduate dental students in Nepal acquire much of their basic knowledge about dental implants during their internship program. They have perceived the need and shown a positive attitude towards gaining more information about dental implant procedures through various sources.…”
Section: Discussionmentioning
confidence: 99%